Medicinal Plant Images - Cock, Ian E (Pharmacognosy Communications)
Eremophila maculata (Ker Gawl.) F. Muell. (Family Scrophulariaceae) is an endemic Australian plant that was used in traditional First Australian medicine to treat a wide variety of ailments.1 Additionally, many other members of the genus Eremophila also have traditional medicinal uses. The genus consists of more than 200 species that grow in semi-arid and arid regions of Australia. Multiple Eremophila spp. are used as traditional medicines by the First Australians in the areas in which they grow to treat diverse conditions including uses as antibacterial, antifungal, antiviral, antioxidant, anti-diabetic, and anti-inflammatory therapies, as well as for their cardio-protective properties. The antibacterial properties of Eremophila spp. have been relatively well studied and the several bioactive terpenoids have been identified. This photograph was taken in the Australian Arid Lands Botanic Garden, Port Augusta, Australia, in January 2021 by Ian Cock.